The effect of work discipline and physical work environment on employee performance at PT. Jaya Persada Indonesia East Jakarta - Andayani, Kemas Vivi; Tibaat, Malik Fadhli (Journal of Economics and Business Letters, 2023)
This research aims to determine how the influence of work discipline and physical work environment on the performance of employees at PT. Jaya Persada Indonesia East Jakarta, to find out how the influence of work discipline on employee performance at PT. Jaya Persada Indonesia East Jakarta, and to find out how the physical work environment influences the performance of employees at PT. Jaya Persada Indonesia. The research method used in this study is a quantitative method with an associative approach. The data collection method used is a questionnaire, using a saturated sampling technique or the entire population as a sample, namely 63 respondents. The analytical method used in this study is the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression test, correlation coefficient, coefficient of determination, T-test, and F test. Partial work discipline variable (XI) obtained t count > t table (6.805 > 1.670). This is also reinforced by a significant value of 0.000 <0.005. This means that work discipline has a positive effect on employee performance. The statistical test of the physical work environment variable (X2) obtained the t count > t table (11.651 > 1.670). This was also reinforced by a significant value of 0.001 <0.05. It means that the physical work environment significantly affects employee performance. Simultaneous hypothesis testing obtained f count > f table or (96,311 > 3,150). This was also reinforced by a significant value of 0.000 <0.05. So it can be said that work discipline and physical work environment significantly affect employee performance. The coefficient of determination obtained an R square value of 0.701, meaning that work discipline and the physical work environment contribute 70.1% to employee performance. At the same time, the remaining 29.9% is influenced by other factors not examined in this study.